KUTAI LOTION LIMBAH KULIT PETAI (Parkia specio SEBAGAI PRODUK LOSION KULIT (Skin Lotion ) - Fitriana Ikhtiarinawati Fajrin; Ida Susila (Journal of Research and Technology, 2018)
The skin is an organ of the human body that functions to protect from outside influences. Damage to the skin will interfere with human health so that the skin needs to be protected and maintained its health. One of the things that causes skin damage is freeradicals. To prevent skin damage from free radicals, an antidote is needed, namely antioxidant compounds. One source of natural antioxidants is petai bark extract (Parkia speciosa). In this study, petai bark extraction was carried out by using ethanol solvent.The dried petai powder was macerated with ethanol solvent for 24 hours, then solvent separation was carried out by using a rotary evaporator so that the extraction was concentrated green. The antioxidant activity in petai bark extract was observed through qualitative tests using DPPH reagent. The test results showed that the positive petai bark extract had antioxidant activity. The final stage of this study was to mix petai bark extract with skin lotion preparations. Based on the results of this study, petai bark waste which was originally of non economic value can be optimized to be an unique product and has high benefits. Keywords: Antioxidants, Ethanol Extract, Lotion, Petai Bark (Parkia speciosa).